Children during the Holocaust - Heberer, Patricia (Documenting life and destruction, 2011)
Children in the early years of antisemitic persecution -- Children and the war -- Lives in the balance: escape and deportation -- Children in the world of the ghetto -- Children in the concentration camp universe -- Children in the web of racial hygiene policy -- The lives of others: "Aryan" children and the Nazi regime -- The world of the child -- Children and resistance and rescue -- Elsewhere, perhaps? Children and the end of the Holocaust